The Antecedent of Air Asia Indonesia Brand Trusts on Indonesia Domestic Customer and the Effect of QZ 8501 Disaster to Their Future Trust and Purchase Intention - Harmal, Augy; Hudrasyah, Herry (Journal of Business and Management, 2015)
Abstract.In December, 28th 2014, QZ 8501 which departed from Ir. Djuanda Airport, Surabaya to Changi International Airport, Singapore encountered machine problems because it hit the Cumulonimbus Cloud which engendered stall and finally crashed down near the Cape Pandan, Kalimantan. Many controversies arose after the tragedy such as QZ 8501 flight permission issued by the ministry of Air Transportation, the downfall of the Air Asia Indonesia profits, decreasing number of Air Asia Indonesiaâ€™s load factor and passengers level at the end of 2014 and finally the traumatic problems to the Indonesia society right after the tragedy in terms of their intention to using Air Asia. This study has three aims which are: a) to determine the Domestic customers preferences while choosing Airlines services using Kraskull-Wallist test, b) to understand the current trust and willingness to purchase from the Domestic customers towards Air Asia Indonesia seven months after the tragedy using Qualitative and Quantitative approach and c) trying to examine the relationship between Service Quality, Customer Satisfaction and Corporate Image to the Brand Trust and Purchase Intention towards Air Asia Indonesia from Domestic Customers perspective. The result from this study indicates that a number of common aspects that customers consider while choosing Airlines such as Safety aspects as the main priority. Related to the Customer Brand Trust and Purchase Intention towards Air Asia Indonesia, above 80 percent of respondents still trust and willing to purchase. This research indicates that all of Airlines in Indonesia especially Air Asia Indonesia try to build their new image and get back customers trust by convincing the customers that they already increased their safety especially with the increase of plane accidents happened lately. The flight permission issues for QZ 8501 should be a lesson for all of Airlines in Indonesia to be more submissive to the rules that already made by regulators.Â Keywords : QZ 8501, Air Asia Indonesia, Brand Trust, Purchase Intention, Service Quality, Customer Satisfaction, Corporate Image, Partial Least Square, Kraskull-Wallist,